Scientific data cloud construction and service of Chinese Academy of Sciences - Jianhui LI; Yuanchun ZHOU; Lianglin HU; Feng LIU; Yanhua ZHU; Zhihong SHEN; Zhangsheng WU; Yang ZHANG (大数据)
Scientific Data Resource Integration and Sharing Project is one of the 5 major informatization-specific projects of CAS for the 12th Five-Year Plan period.The overall construction of the project ideas,construction,technical innovation and service innovation,etc.,was summarized.By the end of the project,a distributed mass storage environment with storage capacity of 52 PB was built.At the same time,it provided users with a strong connection between scientific data and literature and a rich visual display platform.The project has initially achieved a multi-level,cross information service system that included the infrastructure cloud service,research data cloud service and data application cloud service.It has gradually become a national science and technology data center for open sharing and service innovation.